1977
DOI: 10.1159/000221972
|View full text |Cite
|
Sign up to set email alerts
|

Amoxycillin and Co-Trimoxazole in Acute Purulent Exacerbations of Chronic Bronchitis

Abstract: 100 hospital patients suffered from acute exacerbations of chronic bronchitis. 50 were treated with amoxycillin in a dose of 500 mg, three times a day for 10 days and the results compared with 50 patients treated with co-trimoxazole in a dose up to 480 mg trimethoprim and 2,400 mg of sulphamethoxazole daily in males, and two thirds of this dose in females. The trial was single-blind. During the acute phase of infection, both treatments were equally effective in clinical improvement, conversion of the sputum fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Our study has established that the combination of rifampicin with trimetho prim reduces the selection of rifampicin-re sistant strains to an acceptable rate, compa rable with the one found in studies with oth er antimicrobial agents, such as streptomy cin [Finland et al, 1946], nalidixic acid [Ronald et al, 1966], sulfonamides [Wil liams et al, 1965], cephaloridine [Stewart and Holt, 1964] carbenicillin [Jones and Lowbury, 1967] and cotrimoxazole [Pines et al, 1977],…”
Section: Discussionsupporting
confidence: 72%
“…Our study has established that the combination of rifampicin with trimetho prim reduces the selection of rifampicin-re sistant strains to an acceptable rate, compa rable with the one found in studies with oth er antimicrobial agents, such as streptomy cin [Finland et al, 1946], nalidixic acid [Ronald et al, 1966], sulfonamides [Wil liams et al, 1965], cephaloridine [Stewart and Holt, 1964] carbenicillin [Jones and Lowbury, 1967] and cotrimoxazole [Pines et al, 1977],…”
Section: Discussionsupporting
confidence: 72%
“…This difference was statistically significant. 70 Chodosh, 52 analyzing long-term follow-up data on a series of trials in AECB, has shown that the mean time from the end of therapy of one exacerbation to the onset of the next may allow more reliable assessment of comparative efficacy. Thus, if the time to relapse after ampicillin therapy (about 200 days) is taken as the index value, ratios for the same periods applicable to other agents can be calculated.…”
Section: New Approaches To 0utco~e Assessmentmentioning
confidence: 99%
“…The presence of salivary amoxicihlin in chronic bronchitis patients could be due to penetration of amoxicillin into sputum through inflamed lung tissue, high intrabronchial concentrations (13) and contamination of saliva by sputum, or even by the dosing and saliva collection techniques. A similar relationship was observed between ampicilhin and its methoxymethyl ester (BL-P1761).…”
Section: Methodsmentioning
confidence: 99%